A coding scheme to clarify teachers' interactive cognitions in noticed classroom management situations from an actor's perspective. (March 2022) - van Driel, Sharisse; Wolff, Charlotte E.; Crasborn, Frank; Brand-Gruwel, Saskia; Jarodzka, Halszka
Abstract: This article presents a coding scheme to clarify teachers' verbalizations of interactive cognitions in classroom management situations noticed from an actor's perspective. Twelve secondary teachers taught a class wearing a front view camera. Classroom management situations they noticed as salient were identified in-action by hand signaling and combined with stimulated recall based on front view videos to explicate accompanying interactive cognitions. Content analysis of verbalized cognitions resulted in a comprehensive coding scheme with four code dimensions: Level of Activated Cognitions, Involved Actor(s), Classroom Management Aspect, Classroom Management Action. The coding scheme contributes to investigating teachers' cognitions accompanying own classroom management behavior in an integrative way. Highlights: Teachers' interactive cognitions in noticed classroom management situations. Verbalizations of interactive cognitions captured from an actor's perspective. Stimulated-recall interviews based on front-view videos. Multi-dimensional coding scheme for clarifying interactive cognitions. Coding scheme for mixed-method investigations across expertise groups.